Measuring Costs and Outcomes of Tele-Intervention When Serving Families of Children who are Deaf/Hard-of-Hearing - Kristina M. Blaiser; Diane Behl; Catherine Callow-Heusser; Karl R. White (International Journal of Telerehabilitation)
Background: Optimal outcomes for children who are deaf/hard-of-hearing (DHH) depend on access to high quality, specialized early intervention services. Tele-intervention – the delivery of early intervention services via telehealth technology - has the potential to meet this need in a cost-effective manner. Method: Twenty-seven families of infants and toddlers with varying degrees of hearing loss participated in a randomized study, receiving their services primarily through TI or via traditional in-person home visits. Pre- and post-test measures of child outcomes, family and provider statisfaction, and costs were collected. Results: The TI group scored statistically significantly higher on the expressive language measure than the in-person group (p =.03). A measure of home visit quality revealed that the TI group scored statistically significantly better on the Parent Engagement subscale of the Home Visit Rating Scales-Adapted & Extended (HOVRS-A+; Roggman, et al., 2012). Cost savings associate with providing services via TI increased as the intensity of service delivery increased. Although most providers and families were positive about TI, there was great variability in their perceptions. Conclusions: Tele-intervention is a promising cost-effective method for delivering high quality early intervention services to families of children who are DHH.